(untitled) (Journal of Engineering Science, 2022)
Mayur River, locating north western side of Khulna, has enormous significance from numerous points of views like water reservoir, navigation etc. Unfortunately latrge scale water quality degradation took place due to pollution as a result of human interruption, unplanned and untreated crude dumping of domestic, industrial and household waste into it. The aim of this study are to carry out the temporal and spatial water quality assessment of selected locations of Mayur River. The water quality was found “Very Bad” in March-2019, April-2019 and May-2019 from station 1 to station 8 except station 4 in June-2019. From July-2019 to February-2020 the water quality was found “Bad” with some exception like station 6 in February-2020. For all the stations (S1 to S8) the regression equations indicate upward regression line and the R2 values show the plotted data fits the regression model ranging 34.28% to 64.21%. Journal of Engineering Science 13(1), 2022, 89-96